First record of shield-backed katydids in Madagascar with the description of a new genus and three new species (Orthoptera: Ensifera: Tettigoniidae: Tettigoniinae: Arytropteridini) - Hugel, Sylvain (Zootaxa, 2019)
Shield-backed katydids of tribe Arytropteridini Caudell, 1908 are recorded for the first time in Madagascar. The new genus Toliaridectes n. gen. is proposed to include three new species from the south west of the island: Toliaridectes meridionalis n. gen. n. sp., Toliaridectes wendenbaumi n. gen. n. sp. and Toliaridectes antsycurvis n. gen. n. sp.. Elements of biology of Toliaridectes n. gen. are given and the call of Toliaridectes antsycurvis n. gen. n. sp. is described. The taxonomic position of Arytropteridini is discussed.